Ophthalmic manifestations of Heimler syndrome due to PEX6 mutations. (4th May 2018) - Wangtiraumnuay, Nutsuchar; Alnabi, Waleed Abed; Tsukikawa, Mai; Thau, Avrey; Capasso, Jenina; Sharony, Reuven; Inglehearn, Chris F.; Levin, Alex V.
ABSTRACT: Background/Aims : Pigmentary retinal dystrophy and macular dystrophy have been previously reported in Heimler syndrome due to mutations in PEX1 . Here we reported the ocular manifestations in Heimler syndrome due to mutations in PEX6. Materials and methods : Medical records were reviewed to identify patient demographics, ophthalmic and systemic findings, and results of diagnostic testing including whole genome sequencing. Results : Patient 1 is 12-year-old boy with a novel mutation c.275T>G (p.Val92Gly) and known mutation c.1802G>A (p.Arg601Gln) in PEX6 . Patient 2 is a 7-year-old girl with the same known c.1802G>A (p.Arg601Gln) mutation and another novel missense mutation c.296G>T (p.Arg99Leu). Both patients exhibited a pigmentary retinopathy. Visual acuity in patient 1 was 20/80 and 20/25 following treatment of intraretinal cystoid spaces with carbonic anhydrase inhibitors, while patient 2 had visual acuity of 20/20 in both eyes without intraretinal cysts. Fundus autofluorescence showed a multitude of hyperfluorescent deposits in the paramacular area of both eyes. OCTs revealed significant depletion of photoreceptors in both patients and macular intraretinal cystoid spaces in one patient. Full field electroretinograms showed normal or abnormal photopic but normal scotopic responses. Multifocal electroretinograms were abnormal. Conclusions : Heimler syndrome due to biallelic PEX6 mutations demonstrates a macular dystrophy with characteristic fundus autofluorescence and may be complicated by intraretinal cystoid spaces.